The Use of the Scramble Method to Develop History Learning Activities at SMA Negeri 22 Seram Bagian Barat - Takimpo, Jamal; Wally, Diana; Latupeirissa, Ece; Hetharion, Bety D. S.; Acim, Acim (Riwayat: Educational Journal of History and Humanities, 2023)
The learning activity in history at SMA Negeri 22 Seram Bagian Barat is still low, and the teaching methods used so far are mostly lectures and question-and-answer sessions that do not actively engage students. This study aims to determine how the use of the scramble method can increase students learning activity in history lessons. The method used is Classroom Action Research (CAR) conducted in two cycles. The subjects of the study were 30 students of grade XI. The results showed an increase in the percentage of student learning activities from cycle I to cycle II. In cycle I, the average student activity in the first meeting was 55.4%, increasing to 62.7% in the second meeting. In cycle II, the first meeting reached 70.1% and the second meeting 76.3%. The percentage increase in learning activity between cycle I and cycle II was 20.9%. Based on these results, it can be concluded that the use of the scramble method is effective in fostering learning activity in history at SMA Negeri 22 Seram Bagian Barat.